Organic positive electrode material of ion battery and preparation method of organic positive electrode material

By developing organic positive electrode materials of quinone polymer ion batteries with specific spatial structures, the problem of single and soluble quinone positive electrode materials in the prior art is solved, and good electrochemical performance and stable cycling performance in multivalent ion batteries are achieved.

CN119638986AActive Publication Date: 2025-03-18YANSHAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411826602.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In existing ion batteries, the quinone organic positive electrode materials are single types and are easily soluble in electrolytes, resulting in loss of active substances, and poor stability of multivalent ions embedded, affecting battery performance.

Method used

A quinone polymer ion battery organic positive electrode material with a specific spatial structure was developed. Through the condensation reaction of 2,6-halo-1,4-benzoquinone derivative and the substituted cyclic diamine derivative, a positive electrode material with a polymer chain with a multi-bending configuration is prepared, which is difficult to dissolve in the electrolyte and easy to form aggregated particles.

Benefits of technology

It realizes good electrochemical performance in multivalent ion batteries, inhibits the loss of active substances, has stable rate performance and high long cycle capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638986A_ABST
    Figure CN119638986A_ABST
Patent Text Reader

Abstract

The invention provides an organic positive electrode material for an ion battery and a preparation method of the organic positive electrode material, and the organic positive electrode material belongs to a quinonamine polymer and can be easily coated on a metal current collector. The organic positive electrode material takes quinone carbonyl as a redox site, and a polymeric chain of the organic positive electrode material has a multi-bending configuration, is easy to form aggregated particles, is insoluble in electrolyte, can effectively inhibit the loss of active substances, and also can show good electrochemical performance in a multivalent ion battery. According to the preparation method, 2, 6-halogenated (or hydroxyl)-1, 4-benzoquinone derivatives and ortho-substituted cyclic diamine derivatives are used as reaction raw materials for condensation reaction to prepare the compound. Experiments prove that the organic positive electrode material shows good capacity performance and cycle performance in a multivalent ion battery, for example, the highest specific discharge capacity of the poly (2, 6-dichloro-1, 4-benzoquinone-1, 2-cyclohexane diamine) positive electrode material can reach 266mAh g <-1 > under the current density of 0.02 Ag <-1 > in a zinc ion battery. And the discharge specific capacity reaches 114mAh g <-1 > under the current density of 0.1 Ag <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an organic positive electrode material for an ion battery and a preparation method thereof. Background Art

[0002] Organic cathode materials are in line with the concept of sustainable development and are highly promising cathode materials for ion batteries. The development of organic cathode materials is of great significance for the replacement of energy storage materials and the recycling and degradation of battery materials. The quinone carbonyl group and the phenoloxy group are a pair of redox pairs with excellent reversibility, which can show good redox properties and are suitable as active sites for ion battery cathode materials. The synthesis method of quinone organic cathode materials is simple and the structure modification is easy, which is conducive to the development of new structures. Therefore, they show great application potential and have great application potential in energy storage fields such as ion batteries and supercapacitors.

[0003] However, in ion batteries, the mainstream positive electrode materials that are currently widely used mainly include vanadium-based positive electrode materials, manganese-based positive electrode materials and Prussian blue derivative positive electrode materials. There are relatively few organic positive electrode materials, especially quinone-based organic positive electrode materials, which are relatively single in type. The development of new quinone-based organic positive electrode materials will play a driving role in promoting the development and application of a new generation of ion batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a positive electrode material with a specific spatial structure.

[0005] To achieve the above object, the scheme of the present invention is as follows:

[0006] The present invention provides an organic positive electrode material for an ion battery, and the structural formula of the organic positive electrode material is:

[0007]

[0008] Where n is a natural number greater than or equal to 1; the structure of A is R1 is any one or more of H, alkyl derivatives, aryl derivatives, alkoxy, alkylthio, acyl, ketocarbonyl, and nitro; R2 is any one or more of H, alkyl derivatives, aryl derivatives, and ketocarbonyl derivatives.

[0009] The present invention also provides a method for preparing the organic positive electrode material for an ion battery, which comprises the following steps: dissolving a 2,6-halogenated-1,4-benzoquinone derivative or a 2,6-hydroxy-1,4-benzoquinone derivative and an ortho-substituted cyclic diamine derivative in a reaction solvent for a condensation reaction; filtering after the reaction is completed and cooled to obtain a filter cake; washing the filter cake with a washing solvent and drying the filter cake to obtain the organic positive electrode material for an ion battery.

[0010] Furthermore, the method specifically includes the following steps: dissolving 2,6-halogenated-1,4-benzoquinone derivative or 2,6-hydroxy-1,4-benzoquinone derivative and ortho-substituted cyclic diamine in a reaction solvent at a ratio of 0.1 gram to 2.9 gram of ortho-substituted cyclic diamine derivative per gram of 2,6-halogenated-1,4-benzoquinone derivative to 5 mL to 200 mL of reaction solvent, and then reacting at 20° C. to 150° C. for 1 h to 72 h in an air environment or under the protection of an inert gas; after the reaction is completed and cooled, filtering is performed to obtain a filter cake; the filter cake is washed with a washing solvent and then dried to obtain a black solid powder, thereby obtaining the organic positive electrode material for the ion battery.

[0011] Furthermore, the 2,6-halogenated-1,4-benzoquinone derivative or 2,6-hydroxy-1,4-benzoquinone derivative includes 2,6-difluoro-1,4-benzoquinone or a substituted derivative thereof, 2,6-dichloro-1,4-benzoquinone or a substituted derivative thereof, 2,6-dibromo-1,4-benzoquinone or a substituted derivative thereof, 2,6-diiodo-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6-chloro-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6-bromo-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro- -6-iodo-1,4-benzoquinone or a substituted derivative thereof, 2-chloro-6-bromo-1,4-benzoquinone or a substituted derivative thereof, 2-chloro-6-iodo-1,4-benzoquinone or a substituted derivative thereof, 2-bromo-6-iodo-1,4-benzoquinone or a substituted derivative thereof; wherein the 3,5-substituent R1 of the 2,6-halo-1,4-benzoquinone derivative or the 2,6-hydroxy-1,4-benzoquinone derivative is any one or more of H, alkyl derivatives, aryl derivatives, alkoxy, alkylthio, acyl, ketocarbonyl, and nitro.

[0012] Furthermore, the ortho-substituted cyclic diamine derivative is wherein the substituent R2 is any one or more of H, alkyl derivatives, aryl derivatives, and ketocarbonyl derivatives.

[0013] Furthermore, the reaction solvent is a mixed solvent of one or more of methanol, ethanol, isopropanol, n-butanol, N,N-dimethylformamide or N-methylpyrrolidone.

[0014] Furthermore, the washing solvent is one or more of methanol, ethanol, isopropanol, isobutanol, tetrahydrofuran, N,N-dimethylformamide, N-methylpyrrolidone or deionized water.

[0015] Furthermore, the inert gas is a mixed gas of one or more of nitrogen, helium and argon.

[0016] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:

[0017] The present invention provides an organic positive electrode material for an ion battery and a preparation method thereof. The preparation method of the organic positive electrode material for an ion battery is simple and feasible. The prepared organic positive electrode material is easy to coat on a metal current collector, and its polymer chain has a multi-bend configuration, is easy to form aggregated particles, is difficult to dissolve in an electrolyte, can effectively inhibit the loss of active substances, and can also exhibit good electrochemical properties in multivalent ion batteries. This type of organic positive electrode material uses quinone carbonyl as a redox site, and its configuration is also suitable for stable embedding of multivalent ions, and can also exhibit good electrochemical properties in multivalent ion batteries. Experiments have shown that, taking poly (2,6-dichloro-1,4-benzoquinone-1,2-cyclohexanediamine) as an example, in zinc ion battery applications, at 0.02Ag -1 The highest discharge capacity at current density can reach 266 mAh g -1 . At 0.1Ag -1 The discharge capacity at the current density is 114 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0018] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.

[0019] Figure 1 This is the synthesis route of the organic positive electrode material for ion batteries prepared in Example 1 of the present invention;

[0020] Figure 2 is an X-ray diffraction pattern of the organic positive electrode material for an ion battery prepared in Example 1 of the present invention;

[0021] Figure 3 is a scanning electron microscope image of the organic positive electrode material for an ion battery prepared in Example 1 of the present invention;

[0022] Figure 4 is a transmission electron microscope image of the organic positive electrode material for an ion battery prepared in Example 1 of the present invention;

[0023] Figure 5 This is an infrared spectrum of the organic cathode material for an ion battery prepared in Example 1 of the present invention;

[0024] Figure 6 The organic positive electrode material for ion batteries prepared in Example 1 of the present invention has a high conductivity at 0.1 mV s in zinc ion batteries. -1 , 0.2mV s -1 , 0.3mV s -1 , 0.4mV s -1, 0.5mV s -1 , 0.6mV s -1 , 0.8mV s -1 , 1mV s -1 Cyclic voltammetry curves at different scan rates;

[0025] Figure 7 The organic positive electrode material for ion batteries prepared in Example 1 of the present invention is used in zinc ion batteries at 0.02Ag -1 , 0.05Ag -1 , 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 The rate performance under the current density is 266 mAh g -1 , 163mAh g -1 , 114mAh g -1 , 75mAh g -1 , 40mAh g -1 , and 24mAh g -1 When the current density drops back to 0.02Ag -1 When the discharge capacity is restored to 163 mAh g -1 ;

[0026] Figure 8 The organic positive electrode material for the ion battery prepared in Example 1 of the present invention is 0.1Ag in the zinc ion battery -1 Long cycle diagram after 500 charge and discharge cycles at the current density; DETAILED DESCRIPTION

[0027] The inventors found that in the prior art, when quinone-based organic positive electrode materials are applied to ion batteries, small molecule quinone derivative-based positive electrode materials are easily dissolved in the electrolyte, which can easily cause the loss of positive electrode active substances. In addition, the molecular structure of the organic positive electrode material also plays a key role in the embedding stability of multivalent ions, affecting the performance of the battery. After research, the inventors have developed a new type of quinone polymer-based organic positive electrode material for ion batteries. The polymer chain of the organic positive electrode material for ion batteries has a multi-bend configuration, is easy to form aggregated particles, is difficult to dissolve in the electrolyte, can effectively inhibit the loss of active substances, and can also show good electrochemical performance in multivalent ion batteries. The rate performance is stable in charge and discharge capacity at various current densities, and also shows a high capacity retention rate in long cycle performance.

[0028] The invention provides a method for preparing an organic positive electrode material for an ion battery. The method comprises the following steps: dissolving a 2,6-halogenated (or hydroxyl)-1,4-benzoquinone derivative and an ortho-substituted cyclic diamine derivative in a reaction solvent to carry out a condensation reaction; after the reaction is completed and cooled, suction filtering is performed to obtain a filter cake; and the filter cake is washed with a washing solvent and then dried to obtain the organic positive electrode material for an ion battery.

[0029] Furthermore, the method specifically includes the following steps: dissolving 2,6-halogenated (or hydroxyl)-1,4-benzoquinone and ortho-substituted cyclic diamine in a reaction solvent at a ratio of 0.1 gram to 2.0 gram of ortho-substituted cyclic diamine derivative per gram of 2,6-halogenated (or hydroxyl)-1,4-benzoquinone derivative in 5 mL to 200 mL of reaction solvent, and then reacting at 20°C to 150°C for 1 hour to 72 hours in an air environment or under the protection of an inert gas; after the reaction is completed and cooled, filtering is performed to obtain a filter cake; the filter cake is washed with a washing solvent and then dried to obtain a black solid powder, namely, the organic positive electrode material for the ion battery is obtained.

[0030] The synthesis route of the organic cathode material for the ion battery is as follows:

[0031]

[0032] Wherein, n is a natural number greater than or equal to 1; X is any one or more of F, Cl, Br, and I; R1 is any one or more of H, alkyl derivatives, aryl derivatives, alkoxy, alkylthio, acyl, ketocarbonyl, and nitro.

[0033] Furthermore, the 2,6-halogenated (or hydroxylated)-1,4-benzoquinone derivative is 2,6-difluoro-1,4-benzoquinone or a substituted derivative thereof, 2,6-dichloro-1,4-benzoquinone or a substituted derivative thereof, 2,6-dibromo-1,4-benzoquinone or a substituted derivative thereof, 2,6-diiodo-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6-chloro-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6-bromo-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6 -iodo-1,4-benzoquinone or a substituted derivative thereof, 2-chloro-6-bromo-1,4-benzoquinone or a substituted derivative thereof, 2-chloro-6-iodo-1,4-benzoquinone or a substituted derivative thereof, 2-bromo-6-iodo-1,4-benzoquinone or a substituted derivative thereof, wherein the 3,5-substituent R1 of the 2,6-halogenated (or hydroxyl)-1,4-benzoquinone derivative is any one or more of H, an alkyl derivative, an aryl derivative, an alkoxy group, an alkylthio group, an acyl group, a ketocarbonyl group, and a nitro group.

[0034] Furthermore, the ortho-substituted cyclic diamine derivative is wherein the substituent R2 is any one or more of H, alkyl derivatives, aryl derivatives, and ketocarbonyl derivatives.

[0035] Furthermore, the reaction solvent is a mixed solvent of one or more of methanol, ethanol, isopropanol, n-butanol, N,N-dimethylformamide or N-methylpyrrolidone.

[0036] Furthermore, the washing solvent is one or more of methanol, ethanol, isopropanol, isobutanol, tetrahydrofuran, N,N-dimethylformamide, N-methylpyrrolidone or deionized water.

[0037] Furthermore, the gas is a mixture of one or more of nitrogen, helium and argon.

[0038] The present invention also provides an organic positive electrode material for an ion battery, such as the organic positive electrode material for an ion battery prepared by the above-mentioned method for preparing the organic positive electrode material for an ion battery.

[0039] Furthermore, the structural formula of the organic positive electrode material of the ion battery is:

[0040]

[0041] Where n is a natural number greater than or equal to 1; the structure of A is R1 is any one or more of H, alkyl derivatives, aryl derivatives, alkoxy, alkylthio, acyl, ketocarbonyl, and nitro; R2 is any one or more of H, alkyl derivatives, aryl derivatives, and ketocarbonyl derivatives.

[0042] The present invention also provides the use of the above-mentioned organic positive electrode material for ion batteries in the field of ion batteries.

[0043] The present invention is described in detail below in conjunction with specific implementation modes.

[0044] Example 1

[0045] 0.21g (1.2mmol) of 2,6-dichloro-1,4-benzoquinone and 0.11g (1mmol) of 1,2-cyclohexanediamine were dissolved in 25mL of anhydrous ethanol and reacted at 78°C for 48h under nitrogen protection. The reaction gradually changed from yellow to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure and washed with deionized water and anhydrous ethanol for 3 times respectively. The filter cake was dried at 80°C for 12h to obtain a black solid powder, which is the organic positive electrode material for ion batteries described in the present invention. In this embodiment, it is specifically named as poly (2,6-dichloro-1,4-benzoquinone-1,2-cyclohexanediamine) positive electrode material.

[0046] Figure 1This is the synthesis route of the organic positive electrode material for the ion battery prepared in this example.

[0047] Figure 2 This is an X-ray diffraction diagram of the organic cathode material for an ion battery prepared in this embodiment. The main diffraction peak in the diagram is at 21°, which is a broad peak. The organic cathode material for an ion battery of the present invention is in an amorphous state.

[0048] Figure 3 This is a scanning electron microscope image of the organic positive electrode material for the ion battery prepared in this example, which is distributed in the form of clustered particles at a microscopic scale.

[0049] Figure 4 The transmission electron microscope image of the organic positive electrode material for the ion battery prepared in this example also shows clustered particles at the nanoscale.

[0050] Figure 5 This is the infrared spectrum of the organic cathode material for ion batteries prepared in this example. The main infrared absorption peak in the figure is in the range of 998cm -1 、1385cm -1 、1725cm -1 、2064cm -1 、5188cm -1 、5370cm -1 and 6760cm -1 about.

[0051] The organic positive electrode material for ion batteries prepared in this example was used as the positive electrode active material for zinc ion batteries. The organic positive electrode material: acetylene black: polyvinylidene fluoride were mixed and ground in a mass ratio of 6:3:1, N-methylpyrrolidone was added dropwise for grinding, and the mixture was coated on a stainless steel mesh and vacuum dried to prepare a positive electrode sheet. A zinc sheet was used as the negative electrode, and 1 mol·L -1 The ZnSO4 solution was used as the electrolyte and the glass fiber was used as the separator. The CR2032 coin battery was assembled and the electrochemical performance was tested.

[0052] Figure 6 The organic positive electrode material for ion batteries prepared in Example 1 of the present invention has a high conductivity at 0.1 mV s in zinc ion batteries. -1 , 0.2mV s -1 , 0.3mV s -1 , 0.4mV s -1 , 0.5mV s -1 , 0.6mV s -1 , 0.8mV s -1 , 1mV s -1 Cyclic voltammetry curve at scanning rate. The battery composition is: positive electrode material ‖ ZnSO4 (1 mol L -1)‖Zn, the oxidation peaks in the figure are around 0.8V and 1.2V, and the reduction peaks are around 0.5V and 0.8V. The redox peaks in the figure are obvious and symmetrical, and the peak positions are stable, indicating that the organic cathode material of the present invention has good cycle reversibility.

[0053] Figure 7 The organic positive electrode material for ion batteries prepared in Example 1 of the present invention is used in zinc ion batteries at 0.02Ag -1 , 0.05Ag -1 , 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 The rate performance under the current density is 266 mAh g -1 , 163mAh g -1 , 114mAh g -1 , 75mAh g -1 , 40mAh g -1 , and 24mAh g -1 When the current density drops back to 0.02Ag -1 When the discharge capacity is restored to 163 mAh g -1 .

[0054] Figure 8 The organic positive electrode material of the ion battery prepared in Example 1 of the present invention is 0.1Ag in the zinc ion battery -1 Long cycle diagram after 500 charge and discharge cycles at the current density. In the figure, the capacity retention rate after 500 charge and discharge cycles is 39%.

[0055] The electrochemical properties such as discharge capacity, rate performance stability, and long cycle capacity retention rate obtained from the above tests are better than those of naphthoquinone, anthraquinone, poly(quinone-4,4'-diaminobiphenyl), poly(quinone-ethylenediamine) and other positive electrode materials. For example, compared with poly(2,5-dichloro-1,4-benzoquinone-1,2-cyclohexanediamine) positive electrode material at 0.02Ag -1 The discharge capacity of the first cycle at the current density is 139 mAh g -1 The organic positive electrode material for the ion battery of the present invention has obvious performance advantages.

[0056] Example 2

[0057] 0.21g (1.2mmol) of 2,6-dichloro-1,4-benzoquinone and 0.11g (1mmol) of 1,2-phenylenediamine were dissolved in 20mL of ethanol and reacted at 78°C for 48h under nitrogen protection. The reaction gradually changed from yellow to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60°C for 12h and other post-treatments to obtain a black solid powder, i.e., the organic positive electrode material for ion batteries described in the present invention.

[0058] The organic positive electrode material of the ion battery prepared in this example was used as the active material of the positive electrode of the zinc ion battery. The organic positive electrode material: acetylene black: polyvinylidene fluoride were mixed and ground in a mass ratio of 6:3:1, N-methylpyrrolidone was added dropwise and ground, and the mixture was coated on a stainless steel mesh and vacuum dried to prepare a positive electrode sheet. A zinc sheet was used as the negative electrode, and 1 mol·L -1 The ZnSO4 solution was used as the electrolyte and the glass fiber was used as the separator to assemble a CR2032 coin battery. The electrochemical performance was tested at 0.02Ag -1 The maximum discharge capacity at this current density is 149 mAh g -1 .

[0059] Example 3

[0060] 0.58g (2.2mmol) of 2,6-dibromo-1,4-benzoquinone and 0.20g (2mmol) of 1,2-cyclopentanediamine were dissolved in 20mL of N,N-dimethylformamide and reacted at 100°C for 24h under argon protection. The reaction gradually changed from brown to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60°C for 12h and other post-treatments to obtain a black solid powder, i.e., the organic positive electrode material for ion batteries described in the present invention.

[0061] Example 4

[0062] 0.29g (1mmol) of 3,5-dimethyl-2,6-dibromo-1,4-benzoquinone and 0.11g (1mmol) of 1,2-phenylenediamine were dissolved in 15mL of N,N-dimethylformamide and reacted at 100°C for 24h under helium protection. The reaction gradually changed from brown to black. After the reaction was completed, the mixture was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60°C for 12h by air blast and other post-treatments to obtain a black solid powder, i.e., the organic positive electrode material for ion batteries described in the present invention.

[0063] Example 5

[0064] 0.71g (2mmol) of 2,6-diiodo-1,4-benzoquinone and 0.14g (1.2mmol) of 1,2-cyclohexanediamine were dissolved in 20mL of N-methylpyrrolidone and reacted at 150°C for 36h. The reaction gradually changed from brown to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60°C for 12h and other post-treatments to obtain a black solid powder, i.e., the organic positive electrode material for ion batteries described in the present invention.

[0065] Example 6

[0066] 0.35 g (2 mmol) of 2,6-dichloro-1,4-benzoquinone and 0.15 g (1.2 mmol) of 1,2-cycloheptanediamine were dissolved in 20 mL of methanol and reacted at 20 ° C for 1 hour under nitrogen protection. The reaction gradually changed from brown to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60 ° C for 12 hours and other post-treatments to obtain a black solid powder, that is, the organic positive electrode material for ion batteries described in the present invention.

[0067] Example 7

[0068] 0.35 g (2 mmol) of 2,6-dichloro-1,4-benzoquinone and 0.44 g (3.2 mmol) of 1,2-cyclooctanediamine were dissolved in 20 mL of isopropanol and reacted at 70 ° C for 72 hours under nitrogen protection. The reaction gradually changed from brown to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60 ° C for 12 hours and other post-treatments to obtain a black solid powder, that is, the organic positive electrode material for ion batteries described in the present invention.

[0069] Example 8

[0070] 0.71 g (2 mmol) of 2,6-diiodo-1,4-benzoquinone and 0.08 g (1 mmol) of 1,2-cyclobutanediamine were dissolved in 20 mL of isobutanol and reacted at 40°C for 36 hours. The reaction gradually changed from brown to black. After the reaction was completed, it was allowed to stand and cool. Finally, the product was filtered by reduced pressure, washed with deionized water and anhydrous ethanol for 3 times respectively, and the filter cake was dried at 60°C for 12 hours to obtain a black solid powder, which is the organic positive electrode material for ion batteries described in the present invention.

[0071] The organic positive electrode material for ion batteries of the present invention can be applied to lithium ion batteries, sodium ion batteries, potassium ion batteries, calcium ion batteries, magnesium ion batteries, aluminum ion batteries, zinc ion batteries, and the like.

[0072] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.

Claims

1. An organic positive electrode material for an ion battery, characterized in that: The structural formula of the positive electrode material is: Where n is a natural number greater than or equal to 1; the structure of A is R1 is any one or more of H, alkyl derivatives, aryl derivatives, alkoxy, alkylthio, acyl, ketocarbonyl, and nitro; R2 is any one or more of H, alkyl derivatives, aryl derivatives, and ketocarbonyl derivatives.

2. The method for preparing an organic cathode material for an ion battery according to claim 1, characterized in that: The method comprises the following steps: A 2,6-halogenated-1,4-benzoquinone derivative or a 2,6-hydroxy-1,4-benzoquinone derivative and an ortho-substituted cyclic diamine derivative are dissolved in a reaction solvent to carry out a condensation reaction; after the reaction is completed and cooled, suction filtration is carried out to obtain a filter cake; the filter cake is washed with a washing solvent and then dried to obtain the organic positive electrode material for the ion battery.

3. The method for preparing the organic positive electrode material for an ion battery according to claim 2, the method specifically comprising the following steps: According to the ratio of 0.1 g to 2.0 g of the ortho-substituted cyclic diamine derivative per gram of 2,6-halogenated 1,4-benzoquinone derivative or 2,6-hydroxy-1,4-benzoquinone derivative to 5 mL to 200 mL of the reaction solvent, 2,6-halogenated 1,4-benzoquinone derivative or 2,6-hydroxy-1,4-benzoquinone derivative and ortho-substituted cyclic diamine are dissolved in the reaction solvent, and then reacted at 20° C. to 150° C. for 1 h to 72 h in an air environment or under the protection of an inert gas; after the reaction is completed and cooled, suction filtration is performed to obtain a filter cake; the filter cake is washed with a washing solvent and dried to obtain a black solid powder, thereby obtaining the organic positive electrode material for the ion battery.

4. The method for preparing an organic positive electrode material for an ion battery according to claim 2, characterized in that: The 2,6-halogenated-1,4-benzoquinone derivative or 2,6-hydroxy-1,4-benzoquinone derivative includes 2,6-difluoro-1,4-benzoquinone or a substituted derivative thereof, 2,6-dichloro-1,4-benzoquinone or a substituted derivative thereof, 2,6-dibromo-1,4-benzoquinone or a substituted derivative thereof, 2,6-diiodo-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6-chloro-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6-bromo-1,4-benzoquinone or a substituted derivative thereof, 2-fluoro-6 -iodo-1,4-benzoquinone or its substituted derivatives, 2-chloro-6-bromo-1,4-benzoquinone or its substituted derivatives, 2-chloro-6-iodo-1,4-benzoquinone or its substituted derivatives, 2-bromo-6-iodo-1,4-benzoquinone or its substituted derivatives; wherein the 3,5-substituent R1 of the 2,6-halo-1,4-benzoquinone derivative or the 2,6-hydroxy-1,4-benzoquinone derivative is any one or more of H, alkyl derivatives, aryl derivatives, alkoxy, alkylthio, acyl, ketocarbonyl, and nitro.

5. The method for preparing an organic cathode material for an ion battery according to claim 2, characterized in that: The ortho-substituted cyclic diamine derivative is wherein the substituent R2 is any one or more of H, alkyl derivatives, aryl derivatives, and ketocarbonyl derivatives.

6. The method for preparing an organic cathode material for an ion battery according to claim 2, characterized in that: The reaction solvent is one or more mixed solvents selected from methanol, ethanol, isopropanol, n-butanol, N,N-dimethylformamide or N-methylpyrrolidone.

7. The method for preparing an organic cathode material for an ion battery according to claim 2, characterized in that: The washing solvent is one or more of methanol, ethanol, isopropanol, isobutanol, tetrahydrofuran, N,N-dimethylformamide, N-methylpyrrolidone or deionized water.

8. The method for preparing an organic cathode material for an ion battery according to claim 3, characterized in that: The inert gas is a mixed gas of one or more of nitrogen, helium and argon.

9. Use of the organic positive electrode material for ion batteries as claimed in claim 1 in the field of ion batteries.

Citation Information

Patent Citations

  • Electrode active material for storage battery device and storage battery device employing electrode active material

    CN105489861A

  • 5,7,12,14-tetranitrogen-6,13-pentacenequinone-based electrode material as well as preparation method and application thereof

    CN108864104A

  • Organic material, BDI system and method for removing metal ions in water body

    CN111607085A

  • Organic positive electrode material and preparation method and application thereof

    CN115000402A

  • Polyquinone amine organic positive electrode material and preparation method thereof

    CN117143335A